RUSSIAN STOCK MARKET: ECONOMICS MUST BE INVESMENT ACTIVE - I. V. Kostikov; M. K. Belyaev (Модернизация, инновация, развитие, 2016)
Russian stock market has not yet become integral part of the country economics. It is characteristic with restricted number of participants, insufficient capacity and depth. Fundamental stock market development tasks are: protection of finance service market consumers and participants; solution of insiders’ information problems; creation of a mechanism capable of providing for efficient implementation of legal norms; creation of a juridical system capable of solving economic disputes. The investment innovation problem demands that the set of Russian export products be considerably enlarged and production base of all industries, those traditional included, be reorganized at the state level.